Digital innovations for customer engagement, management, and organizational improvement - Sandhu, Kamaljeet, 1970- (Advances in business strategy and competitive advantage., 2020)
"This book discusses and strategizes the latest technologies and innovations and their integration, implementation, and use in businesses, as well as lifelong learning strategies in a digital environment"--